Real-world Effectiveness of Sofosbuvir/Velpatasvir for Treatment of Chronic Hepatitis C in British Columbia, Canada: A Population-Based Cohort Study. (29th February 2020) - Wilton, James; Wong, Stanley; Yu, Amanda; Ramji, Alnoor; Cook, Darrel; Butt, Zahid A; Alvarez, Maria; Binka, Mawuena; Darvishian, Maryam; Jeong, Dahn; Bartlett, Sofia R; Pearce, Margo E; et al.
Abstract: Background: Clinical trials show high efficacy of sofosbuvir/velpatasvir (SOF/VEL), but there are limited data from "real-world" settings. We aimed to evaluate SOF/VEL effectiveness for all hepatitis C virus (HCV) genotypes (GTs) in British Columbia (BC), Canada. Methods: We used the BC Hepatitis Testers Cohort, which includes all HCV cases in the province (1990–2015) linked to administrative databases, including prescriptions to end of 2018. We measured sustained virologic response (SVR; negative RNA ≥10 weeks after treatment end) and identified characteristics associated with non-SVR. Conservatively, we excluded individuals with no assessment for SVR if their last RNA test after treatment initiation was negative (but included if positive). Results: Of 2821 eligible participants, most were infected with GT1 (1076, 38.1%) or GT3 (1072, 38.0%), and a minority (278, 9.9%) were treated with RBV. SVR was 94.6% (2670/2821) overall and 94.5% (1017/1076) for GT1, 96.4% (512/531) for GT2, and 93.7% (1004/1072) for GT3. When disaggregated by GT, treatment regimen, and cirrhosis/treatment experience, SVR was lowest (30/40, 75.0%) among treatment-experienced GT3 individuals treated with RBV. Characteristics associated with non-SVR in multivariable analysis included younger age, RBV addition, and being a person with HIV (PWH) or who injects/injected drugs (PWID). When treatment regimen (±RBV) was removed from multivariable model, treatment experience was associated with non-SVR for GT3. Of 151 non-SVR individuals, 56.3% were nonvirological failures (treatment incomplete/no assessment for SVR) and 43.7% were virological failures (nonresponse/relapse). A disproportionately high percentage of non-SVR among PWID was due to nonvirological failure. Conclusions: SOF/VEL was highly effective in this "real-world" population-based cohort. Additional support is required for PWID/PWH to reach SVR.